2018
DOI: 10.1007/s12664-018-0850-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for inflammatory bowel disease: A prospective multi-center study

Abstract: This study highlights association between socioeconomic, dietary factors, appendectomy, and family history as risk factors for IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…Theirs is a fascinating finding, but recent data have suggested that the disease does not necessarily favor urban areas. 5,6 Wherever the metals are coming from, this study strengthens the connection of IBD risk with the mothers of affected individuals. The finding of metals that can be tracked to the in utero state suggests that the offspring who will ultimately present with IBD and have high values of these metals are likely acquiring these metals from their mothers.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Theirs is a fascinating finding, but recent data have suggested that the disease does not necessarily favor urban areas. 5,6 Wherever the metals are coming from, this study strengthens the connection of IBD risk with the mothers of affected individuals. The finding of metals that can be tracked to the in utero state suggests that the offspring who will ultimately present with IBD and have high values of these metals are likely acquiring these metals from their mothers.…”
supporting
confidence: 62%
“…Regardless, smoking does not even seem to be associated with Crohn's disease in China or India where IBD is on the rise, likely in the absence of NOD2 mutations. 5,13 Torres et al 4 present the premise that "biomarkers are needed to identify persons at risk for developing inflammatory bowel diseases." Until the tools are available to truly prevent Crohn's disease evolution, at best we can say that biomarkers are needed to help expand our diagnostic armamentarium.…”
mentioning
confidence: 99%
“…Dietary habits differ between the SA sub-groups and might explain some of the observed differences. A recent study of IBD patients in India suggested vegetarianism maybe protective in this cohort[31]. As vegetarianism is higher in Gujarati populations (North Indians), who form the predominant ethnic group in North West London and Leicester, we would have expected a lower not higher UC incidence rates for these regions[32,33].…”
Section: Discussionmentioning
confidence: 85%
“…Amarapurkar A. et al reported that the VD constitutes a risk factor for CD and protects from UC [94]. The study does not show the impact of a vegetarian diet on the course of IBD.…”
Section: Vegetarian Dietsmentioning
confidence: 65%